Preclinical pharmacokinetic modeling and clinical translation of SIG001, a novel anti-cancer therapeutic antibody targeting on cancer-derived sialylated IgG - Qingyu Yao; Chen Liu; Shenghua Zhang; Yaou Liu; Ying Zhou; Xiaoyan Qiu (Frontiers in Pharmacology, 2026)
Introduction Sialylated immunoglobulin G (SIA-IgG) has emerged as a novel therapeutic target selectively overexpressed in epithelial-derived malignancies. The humanized monoclonal antibody SIG001 binds specifically to tumor-associated SIA-IgG and is regarded as a promising first-in-class candidate for the broad-spectrum treatment of epithelial cancers. Methods The pharmacokinetic (PK) behavior of SIG001 was evaluated in both cynomolgus monkeys and mice following intravenous administration. Utilizing modeling approaches, we projected the first-in-human (FIH) starting dose and the human pharmacologically active dose (PAD) from preclinical datasets. Results In cynomolgus monkeys, single-dose PK was assessed at 5, 15, and 30 mg/kg, while in mice, doses of 5, 10, and 20 mg/kg were investigated. Data from both species were well characterized by a two-compartment model with linear elimination kinetics; human PK parameters were extrapolated from the monkey studies. In vitro studies demonstrated that SIG001, at concentrations up to 50 μg/mL, did not elicit significant cytokine release from human peripheral blood mononuclear cells (PBMCs), establishing this concentration as a safety threshold for FIH dose estimation. Based on simulations incorporating moderate PK variability, a maximum recommended starting dose of 0.15 mg/kg, administered biweekly, was identified. Efficacy studies in murine xenograft models revealed a plateaued, dose-dependent antitumor response across the range of 2.5–10 mg/kg, indicative of maximal receptor occupancy and a saturated therapeutic effect. The translational scaling of murine PK profiles yielded human equivalent doses (HEDs), with predicted PAD values ranging from 1.8 to 7.0 mg/kg. Conclusion The preclinical investigations delineate the PK profile and antitumor activity of SIG001. The quantitative translation of animal data into human PK and exposure–response expectations provides a rational foundation for clinical development and supports informed decision-making in the design of early-phase trials.